2006
DOI: 10.4049/jimmunol.176.3.1355
|View full text |Cite
|
Sign up to set email alerts
|

Flightless I Homolog Negatively Modulates the TLR Pathway

Abstract: To date, much of our knowledge about the signaling networks involved in the innate immune response has come from studies using nonphysiologic model systems rather than actual immune cells. In this study, we used a dual-tagging proteomic strategy to identify the components of the MyD88 signalosome in murine macrophages stimulated with lipid A. This systems approach revealed 16 potential MyD88-interacting partners, one of which, flightless I homolog (Fliih) was verified to interact with MyD88 and was further cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 43 publications
2
87
0
Order By: Relevance
“…NRX Links Fli-I to MyD88-Recent reports have shown the involvement of Fli-I in the TLR4/MyD88 pathway (17,20). As we identified Fli-I as a novel binding partner of NRX, we hypothesized that NRX may affect the TLR4/MyD88 pathway.…”
Section: (Student's T Test) E Wt or Nrxmentioning
confidence: 89%
See 4 more Smart Citations
“…NRX Links Fli-I to MyD88-Recent reports have shown the involvement of Fli-I in the TLR4/MyD88 pathway (17,20). As we identified Fli-I as a novel binding partner of NRX, we hypothesized that NRX may affect the TLR4/MyD88 pathway.…”
Section: (Student's T Test) E Wt or Nrxmentioning
confidence: 89%
“…On the basis of the results of co-immunoprecipitation analyses, Wang et al (20) showed that MyD88 and Fli-I form a complex; however, whether the interaction is direct or not was not determined. Using purified recombinant proteins, we clearly showed that the association between MyD88 and Fli-I is not direct but requires NRX as a link (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations